Electrolyte-resistant high-fluorine-content fluororubber for lithium battery

By preparing high-fluorine-content fluororubber, the problem that existing materials cannot simultaneously achieve low high-temperature compression set, excellent volume resistivity, and low immersion expansion rate has been solved, resulting in excellent vulcanization and physical-mechanical properties, making it suitable for power battery seals.

CN119391110APending Publication Date: 2025-02-07ZHEJIANG JUSHENG FLUOROCHEM

Patent Information

Application Number
CN202411518556.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing fluororubber materials for lithium batteries cannot simultaneously achieve low high-temperature compression set, excellent material volume resistivity, and low immersion volume expansion rate, making them unsuitable for different lithium electrolyte environments.

Method used

Using high-fluorine-content fluororubber raw material as raw material, and through a series of additives, the fluororubber prepared has a high-temperature compression set of ≤20%, a material volume resistivity of ≥2.4×10¹²Ω·cm, and an immersion volume expansion rate of ≤30%.

Benefits of technology

The prepared fluororubber has excellent vulcanization and physical and mechanical properties, and is suitable for sealing components of power batteries. It achieves a high-temperature compression set of ≤20%, a material volume resistivity of ≥2.4×10¹²Ω·cm, and an immersion volume expansion rate of ≤30%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391110A_ABST
    Figure CN119391110A_ABST
Patent Text Reader

Abstract

The invention provides electrolyte-resistant high-fluorine-content fluororubber for a lithium battery, and belongs to the technical field of new energy battery materials. Specifically, vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene are used as polymerization monomers, in a deoxidized high-purity water environment, a pH buffer agent, a chain transfer agent and an initiator are added for polymerization reaction to prepare raw rubber, and the fluororubber raw rubber prepared by the method has high fluorine content. The electrolyte-resistant high-fluorine-content fluororubber for the lithium battery, which is prepared by taking the high-fluorine-content fluororubber raw rubber as a raw material and adding a series of auxiliaries for mixing and refining rubber, is suitable for the field of sealing elements of power batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy battery materials, in particular to an electrolyte-resistant high-fluorine-content fluororubber for lithium batteries. Background Art

[0002] The electrolyte has a great influence on the performance of lithium batteries, and excellent performance electrolyte rubber seals are of great significance to the normal operation of lithium batteries. The electrolyte composition is complex, and the material requirements for the seal are very high. At present, the main materials for the seal are peroxide high fluorine rubber, nitrile rubber, perfluoroether rubber and silicone rubber. Among them, peroxide high fluorine rubber stands out because it has low compression permanent deformation, excellent insulation performance and low electrolyte volume expansion rate. At present, peroxide high fluorine rubber is widely used in the field of seals for power batteries. However, in the face of the rapid development of the power battery industry, the performance requirements for peroxide high fluorine rubber are getting higher and higher, especially the tolerance to the electrolyte. Therefore, it is urgent to develop a new method for preparing peroxide high fluorine rubber to meet the demand for sealing ring products suitable for different lithium electrolyte environments.

[0003] Patent document CN115584141A discloses a bisphenol high fluorine rubber compound resistant to lithium battery electrolyte and its preparation method. The main improvement is that the dechlorinated bisphenol AF salt vulcanizer and functional additive N325 carbon black are used to reduce the compression permanent deformation. The bisphenol high fluorine rubber is mixed by using the premixed rubber of bisphenol high fluorine rubber, which reduces the volume expansion rate of high fluorine rubber in the electrolyte. Bisphenol high fluorine rubber with a fluorine content of 70% to 71% is selected and mixed using the above improved method to obtain a compound with a high temperature (200℃×70h) compression permanent deformation of 19% to 24% and a volume expansion rate in the electrolyte of 22% to 29%. However, the volume resistance of the assembled lithium battery seal is small (2.2×10 10 Ω·cm~1.4×10 12 Ω·cm), which cannot meet the electrolyte resistance requirements.

[0004] Patent document CN111269511A discloses an insulating fluororubber material for lithium battery sealing and a preparation method thereof. The main improvement is that 0.75wt%~2.5wt% white carbon black and / or barium sulfate are used as insulating medium for mixing, so that the mixed rubber has excellent electrolyte resistance, and the volume resistance of the material is within 2×10 12 Ω·cm or more, and the high temperature (200℃×70h) compression permanent deformation is less than 20%, which meets the insulation and high temperature resistance performance of the seal. However, after soaking in electrolyte, the expansion rate is high (volume expansion rate is 30%~35%, mass expansion rate is 15%~20%), which affects the performance of the seal.

[0005] The electrolyte-resistant fluororubber required at this stage must meet the following requirements: low high-temperature compression permanent deformation, high material volume resistance, low immersion volume expansion rate, and good vulcanization performance and physical and mechanical properties. However, the mixed fluororubber published in the existing patents cannot take into account the above excellent properties, resulting in each product being unable to be applied to various lithium battery electrolyte environments. It is urgent to find a new preparation method that can improve the comprehensive performance of fluororubber products.

[0006] In view of this, the present invention provides an electrolyte-resistant high-fluorine content fluororubber for lithium batteries. Summary of the invention

[0007] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0008] The purpose of the present invention is to provide a high-fluorine content fluororubber for lithium battery resistant to electrolyte, which is made of high-fluorine content fluororubber raw rubber as raw material, and a series of additives are mixed to prepare the fluororubber, and the high-temperature compression permanent deformation (200℃×70h) of the prepared fluororubber is ≤20%, and the volume resistance of the material is ≥2.4×10 12 Ω·cm, immersion volume expansion rate ≤30%, suitable for the field of power battery seals.

[0009] In order to achieve the above object, the present invention adopts the following technical solutions: A fluorine rubber with high fluorine content and resistant to electrolyte for lithium battery, characterized by comprising the following steps: S1: According to the weight ratio, 600-800 parts of deoxygenated high-purity water, 0.5-2 parts of pH buffer, and 0.1-1 parts of chain transfer agent are added to the polymerization kettle, stirring is started, and the stirring speed is 100-200 rpm. The polymerization kettle is heated to 60-100° C., and a first mixed gas of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene is introduced until the pressure of the polymerization kettle is 2000-3000 kPa, and 0.1-1 parts of initiator are added to initiate the copolymerization reaction; S2: After the polymerization starts, a second mixed gas of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene is introduced, and the pressure of the polymerization kettle is maintained at 2000-3000 kPa. When the consumption of the second mixed gas reaches 150-250 parts, the copolymerization reaction is terminated, the polymerization kettle is depressurized and discharged, and 20-30 parts of a coagulant are added to the obtained emulsion for coagulation and washing, and then treated in an oven to obtain raw rubber; S3: Prepare the following mixing components: 100 parts of raw rubber, 1-2 parts of vulcanizing agent, 3-4 parts of vulcanizing aid, 20-30 parts of filler material MT carbon black N9900, and 0.6-6 parts of processing aid. Add the above components into an internal mixer and mix them. After leaving them at room temperature for 15-30 hours, return them on an open mixer to finally prepare electrolyte-resistant peroxy fluororubber.

[0010] Furthermore, the pH buffer is selected from one of dipotassium hydrogen phosphate, potassium dihydrogen phosphate, and disodium hydrogen phosphate.

[0011] Furthermore, the chain transfer agent is selected from one or more mixtures of ethers, ketones, aromatic hydrocarbons, and alkanes, including one of diethyl ether, propylene oxide, methyl butyl ketone, methyl isobutyl ketone, toluene, xylene, isobutane, and cyclopropane.

[0012] Furthermore, the initiator is selected from one or more mixtures of organic and inorganic peroxides, including one of hydrogen peroxide, ammonium persulfate, potassium persulfate, tert-butyl hydroperoxide, di-tert-butyl peroxide, and dibenzoyl peroxide.

[0013] Furthermore, in step S1, an initiator synergist is added to participate in the polymerization, and the preparation method thereof is as follows: a: Weigh 3-6 parts of p-mercaptoterephthalic acid and 10-20 parts of titanium tetrachloride by mass, place them in a closed reactor, introduce nitrogen to replace the air, then add 100-150 parts of ethanol, mix and stir; pour the mixed solution into a hydrothermal reactor, put it in an oven, adjust the oven temperature to 200-220°C, take it out after crystallization, let it stand and naturally cool to room temperature to obtain a precursor; b: Weigh 5-10 parts of precursor, 100-150 parts of toluene, 0.03-0.7 parts of dicyclopentene methacrylate, and 2-5 parts of sodium ethoxide by mass, place them in a closed reaction kettle, introduce nitrogen to replace the air, adjust the temperature to 60-75°C, and heat for 30-100 minutes; then add 2-6 parts of titanium tetrachloride, heat for 30-60 minutes; distill off the toluene, dry, and obtain an initiator synergist.

[0014] Furthermore, the initiator synergist is added in an amount of 0.1-5wt% of the initiator, and is optimized to be 0.5-2wt%.

[0015] Furthermore, the molar ratio of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene in the first mixed gas is 5-20:50-70:20-30; the molar ratio of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene in the first mixed gas is 15-30:30-50:30-60.

[0016] Furthermore, the coagulant is a mixture of one or more low-valent metal chlorides.

[0017] Furthermore, the vulcanizing agent is a mixture of one or more of triallyl isocyanurate, dicumyl peroxide, and 1,3-bis(tert-butylperoxyisopropyl)benzene.

[0018] Furthermore, the vulcanization aid is a mixture of one or more of trimethylolpropane trimethacrylate, triallyl isocyanurate, and 2,5-di-tert-butylperoxide-2,5-dimethylethane.

[0019] Furthermore, the processing aid is a mixture of one or more of a condensation product of a fatty acid derivative and silicone, palm wax, and stearic acid.

[0020] The synthesis principle of the initiator synergist in the present invention is: (1) p-Mercaptoterephthalic acid reacts with titanium tetrachloride to obtain a mercapto organic titanium metal skeleton, which then undergoes a mercapto-ene addition reaction with dicyclopentene methacrylate, and then undergoes secondary complexation with titanium tetrachloride to obtain a dicyclopentenyl organic titanium metal skeleton; (2) The metal free radical of the initiator is a stable free radical, which couples with the chain growth free radical to generate an oxidized organic metal complex. The organic metal complex of the initiator is equivalent to a chain transfer agent; it dominates the polymerization process and controls the free radical polymerization process of olefin monomers.

[0021] Compared with the prior art, the electrolyte-resistant high-fluorine-content fluororubber for lithium batteries prepared in the embodiment of the present invention has the following beneficial effects: 1. The high-fluorine peroxide fluororubber prepared by the present invention has excellent vulcanization and physical and mechanical properties, the rubber fluorine content is 70%-71%, the tc90 time is ≤2.5min, the tensile strength is ≥20MPa, and the elongation at break is ≥220%; 2. The high-fluorine peroxy fluororubber prepared by the present invention has excellent electrolyte resistance and is suitable for the sealing field of power batteries. The high-temperature compression permanent deformation (200℃×70h) is ≤20%, and the material volume resistance is ≥2.4×10 12 Ω·cm, immersion volume expansion rate ≤30%.

[0022] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which: Figure 1 is the tensile strength curve of the comparative example; Figure 2 This is the vulcanization curve of Example 3. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.

[0025] <Example 1> A method for preparing electrolyte-resistant high-fluorine-content fluororubber for lithium batteries comprises the following steps: S1: 52 kg of deoxygenated high-purity water, 120 g of pH buffer disodium hydrogen phosphate, and 35 g of chain transfer agent isobutane were added to an 80 L stainless steel polymerization kettle, stirring was started, the stirring speed was 180 rpm, the polymerization kettle was heated to 70°C, a first mixed gas of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene was introduced until the pressure of the polymerization kettle was 2400 kPa, the molar ratio of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene in the first mixture was 20:50:30, 20 g of initiator potassium persulfate and 0.2 g of initiator synergist mixture were added to initiate copolymerization; The preparation method of the initiator synergist in this example is: a: Weigh 3 g of p-mercaptoterephthalic acid and 10 g of titanium tetrachloride, place them in a closed reactor, introduce nitrogen to replace the air, then add 100 g of ethanol, mix and stir; pour the mixed solution into a hydrothermal reactor, put it in an oven, adjust the oven temperature to 200°C, take it out after crystallization, let it stand and naturally cool to room temperature to obtain a precursor; b: Weigh 5 g of precursor, 100 g of toluene, 0.03 g of dicyclopentene methacrylate, and 2 g of sodium ethoxide, place them in a closed reaction kettle, introduce nitrogen to replace the air, adjust the temperature to 60°C, and heat for 30 minutes; then add 2 g of titanium tetrachloride and heat for 30 minutes; distill off the toluene, dry, and obtain an initiator synergist.

[0026] S2: After the polymerization starts, the second mixed gas of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene is introduced, and the pressure of the polymerization kettle is maintained at 2400kPa. The molar ratio of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene in the second mixed gas is 20:35:55. When the consumption of the second mixed gas reaches 15kg, the copolymerization reaction is terminated, the polymerization kettle is depressurized and discharged, and the obtained emulsion is added with a coagulant 2kg MgCl2 for coagulation and washing, and then treated in an oven to obtain raw rubber.

[0027] S3: Prepare the following mixing components: (1) 10 kg of raw rubber; (2) 0.15 kg of triallyl isocyanurate vulcanizing agent; (3) 0.3 kg of vulcanizing aid 2,5-di-tert-butyl peroxide-2,5-dimethylethane; (4) 1.5 kg of filler material MT carbon black N9900; (5) 0.5 kg of processing aid octadecanoic acid. Add the above components to an internal mixer and mix them. After leaving them at room temperature for 20 hours, they are remixed on an open mixer to finally obtain electrolyte-resistant peroxy fluororubber.

[0028] <Example 2> A method for preparing electrolyte-resistant high-fluorine-content fluororubber for lithium batteries comprises the following steps: S1: 52 kg of deoxygenated high-purity water, 120 g of pH buffer disodium hydrogen phosphate, and 70 g of chain transfer agent isobutane were added to an 80 L stainless steel polymerization kettle. Stirring was started at a speed of 180 rpm. The polymerization kettle was heated to 75° C. A first mixed gas of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene was introduced until the pressure of the polymerization kettle was 2500 kPa. The molar ratio of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene in the first mixture was 20:50:30. 70 g of initiator ammonium persulfate and 0.4 g of initiator synergist mixture were added to initiate the copolymerization reaction.

[0029] The preparation method of the initiator synergist in this example is: a: Weigh 4 g of p-mercaptoterephthalic acid and 13 g of titanium tetrachloride, place them in a closed reactor, introduce nitrogen to replace the air, then add 115 g of ethanol, mix and stir; pour the mixed solution into a hydrothermal reactor, put it in an oven, adjust the oven temperature to 200°C, take it out after crystallization, let it stand and naturally cool to room temperature to obtain a precursor; b: Weigh 7g of precursor, 115g of toluene, 0.18g of dicyclopentene methacrylate, and 3g of sodium ethoxide, place in a closed reaction kettle, introduce nitrogen to replace the air, adjust the temperature to 65°C, and heat for 50 minutes; then add 3g of titanium tetrachloride and heat for 40 minutes; distill off the toluene, dry, and obtain an initiator synergist.

[0030] S2: After the polymerization starts, the second mixed gas of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene is introduced, and the pressure of the polymerization kettle is maintained at 2500kPa. The molar ratio of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene in the second mixed gas is 20:35:55. When the consumption of the second mixed gas reaches 15kg, the copolymerization reaction is terminated, the polymerization kettle is depressurized and discharged, and the obtained emulsion is added with a coagulant 2kg MgCl2 for coagulation and washing, and then treated in an oven to obtain raw rubber.

[0031] S3: Prepare the following mixing components: (1) 10 kg of raw rubber; (2) 0.1 kg of triallyl isocyanurate vulcanizing agent; (3) 0.3 kg of vulcanizing aid 2,5-di-tert-butyl peroxide-2,5-dimethylethane; (4) 2 kg of filler material MT carbon black N9900; (5) 0.5 kg of processing aid octadecanoic acid. Add the above components to an internal mixer and mix them. After leaving them at room temperature for 20 hours, they are remixed on an open mixer to finally obtain electrolyte-resistant peroxy fluororubber.

[0032] <Example 3> A method for preparing electrolyte-resistant high-fluorine-content fluororubber for lithium batteries comprises the following steps: S1: 52 kg of deoxygenated high-purity water, 60 g of pH buffer disodium hydrogen phosphate, and 35 g of chain transfer agent cyclopropane were added to an 80 L stainless steel polymerization kettle. Stirring was started at a speed of 180 rpm. The polymerization kettle was heated to 70° C. A first mixed gas of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene was introduced into the polymerization kettle at a pressure of 2400 kPa. The molar ratio of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene in the first mixture was 15:60:25. 70 g of initiator tert-butyl hydroperoxide and 0.7 g of an initiator synergist mixture were added to initiate the copolymerization reaction.

[0033] The preparation method of the initiator synergist in this example is: a: Weigh 5 g of p-mercaptoterephthalic acid and 16 g of titanium tetrachloride, place them in a closed reactor, introduce nitrogen to replace the air, then add 140 g of ethanol, mix and stir; pour the mixed solution into a hydrothermal reactor, put it in an oven, adjust the oven temperature to 220°C, take it out after crystallization, let it stand and naturally cool to room temperature to obtain a precursor; b: Weigh 8g of precursor, 140g of toluene, 0.5g of dicyclopentene methacrylate, and 4g of sodium ethoxide, place in a closed reaction kettle, introduce nitrogen to replace the air, adjust the temperature to 70°C, and heat for 65 minutes; then add 5g of titanium tetrachloride and heat for 45 minutes; distill off the toluene, dry, and obtain an initiator synergist.

[0034] S2: After the polymerization starts, the second mixed gas of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene is introduced, and the pressure of the polymerization kettle is maintained at 2400kPa. The molar ratio of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene in the second mixed gas is 25:35:50. When the consumption of the second mixed gas reaches 15kg, the copolymerization reaction is terminated, the polymerization kettle is depressurized and discharged, and the obtained emulsion is added with a coagulant 2kg MgCl2 for coagulation and washing, and then treated in an oven to obtain raw rubber.

[0035] S3: Prepare the following mixing components: (1) 10 kg of raw rubber; (2) 0.15 kg of triallyl isocyanurate vulcanizing agent; (3) 0.3 kg of vulcanizing aid 2,5-di-tert-butyl peroxide-2,5-dimethylethane; (4) 1.5 kg of filler material MT carbon black N9900; (5) 0.55 kg of processing aid octadecanoic acid. Add the above components to an internal mixer and mix them. After leaving them at room temperature for 24 hours, they are remixed on an open mixer to finally obtain electrolyte-resistant peroxy fluororubber.

[0036] <Example 4> A method for preparing electrolyte-resistant high-fluorine-content fluororubber for lithium batteries comprises the following steps: S1: 52 kg of deoxygenated high-purity water, 60 g of pH buffer disodium hydrogen phosphate, and 70 g of chain transfer agent cyclopropane were added to an 80 L stainless steel polymerization kettle. Stirring was started at a speed of 180 rpm. The polymerization kettle was heated to 75° C. A first mixed gas of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene was introduced into the polymerization kettle at a pressure of 2500 kPa. The molar ratio of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene in the first mixture was 15:60:25. A mixture of 20 kg of initiator potassium persulfate and 1 g of initiator synergist was added to initiate the copolymerization reaction.

[0037] The preparation method of the initiator synergist in this example is: a: Weigh 6 g of p-mercaptoterephthalic acid and 20 g of titanium tetrachloride, place them in a closed reactor, introduce nitrogen to replace the air, then add 150 g of ethanol, mix and stir; pour the mixed solution into a hydrothermal reactor, put it in an oven, adjust the oven temperature to 220°C, take it out after crystallization, let it stand and naturally cool to room temperature to obtain a precursor; b: Weigh 10g of precursor, 150g of toluene, 0.7g of dicyclopentene methacrylate, and 5g of sodium ethoxide, place them in a closed reaction kettle, introduce nitrogen to replace the air, adjust the temperature to 75°C, and heat for 100 minutes; then add 6g of titanium tetrachloride and heat for 60 minutes; distill off the toluene, dry, and obtain an initiator synergist.

[0038] S2: After the polymerization starts, the second mixed gas of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene is introduced, and the pressure of the polymerization kettle is maintained at 2500kPa. The molar ratio of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene in the second mixed gas is 25:35:50. When the consumption of the second mixed gas reaches 15kg, the copolymerization reaction is terminated, the polymerization kettle is depressurized and discharged, and the obtained emulsion is added with a coagulant 2kg MgCl2 for coagulation and washing, and then treated in an oven to obtain raw rubber.

[0039] S3: Prepare the following mixing components: (1) 10 kg of raw rubber; (2) 0.1 kg of triallyl isocyanurate vulcanizing agent; (3) 0.3 kg of vulcanizing aid 2,5-di-tert-butyl peroxide-2,5-dimethylethane; (4) 2 kg of filler material MT carbon black N9900; (5) 0.5 kg of processing aid octadecanoic acid. Add the above components to an internal mixer and mix them. After leaving them at room temperature for 24 hours, they are remixed on an open mixer to finally obtain electrolyte-resistant peroxy fluororubber.

[0040] <Comparative Example> A method for preparing electrolyte-resistant high-fluorine-content fluororubber for lithium batteries comprises the following steps: S1: 52 kg of deoxygenated high-purity water, 120 g of pH buffer disodium hydrogen phosphate, and 35 g of chain transfer agent isobutane are added to an 80 L stainless steel polymerization kettle, stirring is started, the stirring speed is 180 rpm, the polymerization kettle is heated to 70°C, and a first mixed gas of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene is introduced until the pressure of the polymerization kettle is 2400 kPa, the molar ratio of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene in the first mixture is 20:50:30, and 20 g of initiator potassium persulfate is added to initiate the copolymerization reaction.

[0041] S2: After the polymerization starts, the second mixed gas of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene is introduced, and the pressure of the polymerization kettle is maintained at 2400 kPa. The molar ratio of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene in the second mixture is 20:35:55. When the consumption of the second mixed monomer reaches 15 kg, the copolymerization reaction is terminated, the polymerization kettle is depressurized and discharged, and the obtained emulsion is added with a coagulant 2 kg MgCl2 for coagulation and washing, and then treated in an oven to obtain raw rubber.

[0042] S3: Prepare the following mixing components: (1) 10 kg of raw rubber; (2) 0.15 kg of triallyl isocyanurate vulcanizing agent; (3) 0.3 kg of vulcanizing aid 2,5-di-tert-butyl peroxide-2,5-dimethylethane; (4) 1.5 kg of filler material MT carbon black N9900; (5) 0.5 kg of processing aid octadecanoic acid, add the above components into an internal mixer and mix, place at room temperature for 20 hours, and then re-mix on an open mixer to finally prepare electrolyte-resistant peroxy fluororubber.

[0043] The test standards and methods for each indicator are as follows: Determination of fluorine content: Use 19F-NMR detection and establish an analytical method by adding an internal standard to accurately test the fluorine content in fluororubber.

[0044] tc90: Heat the mold cavity until the temperature reaches the set value and stabilizes; press the "open / close" switch to open the mold cavity; put a round sample with a diameter of about 38mm, a thickness of 4-5m, and a mass of about 6.5g into the mold cavity; press the "open / close" switch to close the mold cavity, and the test will start automatically. After the set test time is reached, the test will automatically end, and the vulcanization curve will be obtained, and the process positive vulcanization time tc90 will be read.

[0045] Tensile strength and elongation at break: measured in accordance with the provisions of GBT528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", where the specimen type is type 1 and the tensile speed is (500±50) mm / min.

[0046] High temperature compression set: according to GB / T7759-1998 "Determination of compression set of vulcanized rubber and thermoplastic rubber at room temperature, high temperature and low temperature", the test temperature is 200℃ and the test time is 70 hours.

[0047] Material volume resistivity: According to the provisions of GB1410-89 "Test method for volume resistivity and surface resistivity of solid insulating materials", the test voltage is 1000V, and the reading is delayed for 3 seconds.

[0048] Immersion volume expansion rate: The insulating fluororubber of this embodiment was immersed in 85° C. lithium battery electrolyte for 70 hours, and then the volume change of the insulating fluororubber was detected.

[0049] The above examples and comparative examples were tested and analyzed by the above method, and the results are shown in the following table: Example 1 Example 2 Example 3 Example 4 Comparative Example Fluorine content / % 69.87 71.05 72.23 72.69 67.33 tc90 / min 2.07 2.26 2.34 2.39 2.00 Tensile strength / MPa 20.9 21.7 22.5 22.8 20.5 Elongation at break / % 225 231 249 252 230 High temperature compression set (200℃×70h) / % 17 19 20 22 17 Material volume resistance / Ω·cm 2.4×1012 2.6×1012 2.6×1012 2.5×1012 2.4×1012 Immersion volume expansion rate / % 25 25 27 28 22 From the test data of the above embodiments, it can be found that the fluorine content in the rubber is increased to a certain extent after the addition of the initiator synergist, and the immersion volume expansion rate is further improved. This is mainly because the organic metal complex of the initiator synergist is equivalent to the role of a chain transfer agent; it dominates the polymerization process and controls the free radical polymerization process of olefin monomers.

[0050] The above are only embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformations made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A high-fluorine content fluororubber resistant to electrolyte for lithium batteries, characterized in that: The steps include: S1: According to the weight ratio, 600-800 parts of deoxygenated high-purity water, 0.5-2 parts of pH buffer, and 0.1-1 parts of chain transfer agent are added to the polymerization kettle, stirring is started, and the stirring speed is 100-200 rpm. The polymerization kettle is heated to 60-100° C., and a first mixed gas of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene is introduced until the pressure of the polymerization kettle is 2000-3000 kPa, and 0.1-1 parts of initiator are added to initiate the copolymerization reaction; S2: After the polymerization starts, a second mixed gas of vinylidene fluoride, hexafluoropropylene and tetrafluoroethylene is introduced, and the pressure of the polymerization kettle is maintained at 2000-3000 kPa. When the consumption of the second mixed gas reaches 150-250 parts, the copolymerization reaction is terminated, the polymerization kettle is depressurized and discharged, and 20-30 parts of a coagulant are added to the obtained emulsion for coagulation and washing, and then treated in an oven to obtain raw rubber; S3: Prepare the following mixing components: 100 parts of raw rubber, 1-2 parts of vulcanizing agent, 3-4 parts of vulcanizing aid, 20-30 parts of filler material MT carbon black N9900, and 0.6-6 parts of processing aid. Add the above components into an internal mixer and mix them. After leaving them at room temperature for 15-30 hours, return them on an open mixer to finally prepare electrolyte-resistant peroxide fluororubber.

2. The electrolyte-resistant high-fluorine-content fluororubber for lithium batteries according to claim 1, characterized in that: The pH buffer is selected from one of dipotassium hydrogen phosphate, potassium dihydrogen phosphate and disodium hydrogen phosphate.

3. The electrolyte-resistant high-fluorine-content fluororubber for lithium batteries according to claim 1, characterized in that: The chain transfer agent is selected from one of ether, propylene oxide, methyl butyl ketone, methyl isobutyl ketone, toluene, xylene, isobutane and cyclopropane.

4. The electrolyte-resistant high-fluorine-content fluororubber for lithium batteries according to claim 1, characterized in that: The initiator is selected from one of hydrogen peroxide, ammonium persulfate, potassium persulfate, tert-butyl hydroperoxide, di-tert-butyl peroxide, and dibenzoyl peroxide.

5. The electrolyte-resistant high-fluorine-content fluororubber for lithium batteries according to claim 1, characterized in that: In the step S1, an initiator synergist is added in an amount of 0.1-5wt% of the initiator. The preparation method is as follows: a: Weigh 3-6 parts of p-mercaptoterephthalic acid and 10-20 parts of titanium tetrachloride by mass, place them in a closed reactor, introduce nitrogen to replace the air, then add 100-150 parts of ethanol, mix and stir; pour the mixed solution into a hydrothermal reactor, put it in an oven, adjust the oven temperature to 200-220°C, take it out after crystallization, let it stand and naturally cool to room temperature to obtain a precursor; b: Weigh 5-10 parts of precursor, 100-150 parts of toluene, 0.03-0.7 parts of dicyclopentene methacrylate, and 2-5 parts of sodium ethoxide by mass, place them in a closed reaction kettle, introduce nitrogen to replace the air, adjust the temperature to 60-75°C, and heat for 30-100 minutes; then add 2-6 parts of titanium tetrachloride, heat for 30-60 minutes; distill off the toluene, dry, and obtain an initiator synergist.

6. The electrolyte-resistant high-fluorine-content fluororubber for lithium batteries according to claim 1, characterized in that: The molar ratio of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene in the first mixed gas is 5-20:50-70:20-30; the molar ratio of hexafluoropropylene, vinylidene fluoride and tetrafluoroethylene in the second mixed gas is 15-30:30-50:30-60.

7. The electrolyte-resistant high-fluorine-content fluororubber for lithium batteries according to claim 1, characterized in that: The coagulant is a mixture of one or more low-valent metal chlorides and sulfates.

8. The electrolyte-resistant high-fluorine-content fluororubber for lithium batteries according to claim 1, characterized in that: The vulcanizing agent is a mixture of one or more of triallyl isocyanurate, dicumyl peroxide and 1,3-bis(tert-butylperoxyisopropyl)benzene.

9. The electrolyte-resistant high-fluorine-content fluororubber for lithium batteries according to claim 1, characterized in that: The vulcanization aid is a mixture of one or more of trimethylolpropane trimethacrylate, triallyl isocyanurate, and 2,5-di-tert-butylperoxide-2,5-dimethylethane.

10. The electrolyte-resistant high-fluorine-content fluororubber for lithium batteries according to claim 1, characterized in that: The processing aid is a mixture of one or more of a condensation product of a fatty acid derivative and silicone, palm wax, and stearic acid.

Citation Information

Patent Citations

  • Insulating fluororubber material for sealing lithium battery and preparation method thereof

    CN111269511A

  • Lithium battery electrolyte-resistant bisphenol high-fluorine fluororubber compound and preparation method thereof

    CN115584141A

Cited By

  • Electrolyte-resistant high-fluorine-content fluororubber for lithium battery

    WO2026092184A1